Social computing : concepts, methodologies, tools and applications - Dasgupta, Subhasish, 1966- (Hershey, PA : Information Science Reference, 2010)
'This book uncovers the growing and expanding phenomenon of human behavior, social constructs, and communication in online environments, reflecting on social change, evolving networks, media, and interaction with technology and more'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Information technology -- Social aspects; Technological innovations -- Social aspects; Internet -- Social aspects; Technology -- Social aspects